Alterations of redox and iron metabolism accompany the development of HIV latency - Shytaj, Iart Luca; Lucic, Bojana; Forcato, Mattia; Penzo, Carlotta; Billingsley, James; Laketa, Vibor; Bosinger, Steven; Stanić, Mia; Gregoretti, Francesco; Antonelli, Laura; Oliva, Gennaro; Frese, Christian K; et al. (The EMBO journal, 2020)
Abstract HIV-1 persists in a latent form during antiretroviral therapy, mainly in CD4+ T cells, thus hampering efforts for a cure. HIV-1 infection is accompanied by metabolic alterations, such as oxidative stress, but the effect of cellular antioxidant responses on viral replication and latency is unknown. Here, we show that cells survive retroviral replication, both in vitro and in vivo in SIVmac-infected macaques, by upregulating antioxidant pathways and the intertwined iron import pathway. These changes are associated with remodeling of promyelocytic leukemia protein nuclear bodies (PML NBs), an important constituent of nuclear architecture and a marker of HIV-1 latency. We found that PML NBs are hyper-SUMOylated and that PML protein is degraded via the ubiquitin?proteasome pathway in productively infected cells, before latency establishment and after reactivation. Conversely, normal numbers of PML NBs were restored upon transition to latency or by decreasing oxidative stress or iron content. Our results highlight antioxidant and iron import pathways as determinants of HIV-1 latency and support their pharmacologic inhibition as tools to regulate PML stability and impair latency establishment.
Gesehen am 02.07.2020